Characterizing near-surface erosion variability in claypan soils - Mathis, Mark, II (Kansas State University, 2020)
Soil erosion due to an underlying claypan layer ultimately impairs water resources and limits crop yield in agricultural fields. Claypan soils cover approximately 40,469 square kilometers in the United States and are characterized by a highly impermeable layer underlying surficial soil. The objective of this research was to delineate the variability of soil properties, including soil erodibility, in claypan soils. Understanding how soil properties change in the subsurface is critical to understanding the processes exacerbating soil loss in claypan regions. Geophysical methods were used to determine the spatial variability of surface soil (apparent electrical conductivity) and the soil stratigraphy between a high and low apparent electrical conductivity areas (electrical resistivity tomography). Laboratory (erosion function apparatus) and in-situ (“mini” jet erosion test), erosion methods were used to identify the variability in soil erosion with depth in claypan soils. Laboratory test were used to classify and determine the strength and permeability of claypan soils. The results of this study indicate the surficial soil has a higher hydraulic conductivity and is more erodible than the underling claypan layer, which has a lower hydraulic conductivity and is resistant to erosion. As a result, surficial soil is being eroded by the process of undermining due to an underlying impermeable claypan layer. This research is significant because there is limited knowledge of erosion on claypan soils. The knowledge gained from this study will aid in the quantification of erosion on claypan soils in existing erosion models at field and watershed scales.
Keywords: Claypan soils; Erosion